Sedekah Bumi (Earth Charity) as a Means of Social Interaction Amongst Religious Communities in Kalimangli Subvillage, Karang Tengah Village, Tuntang District - Suwartiningsih, Sri; Abraham, Rendy H.; Seba, Roberto Octavianus Cornelis (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Dusun Kalimangli, Karangtengah Village, Tuntang District, Semarang Regency, possesses a local wisdom known as 'sedekah bumi' (earth charity). The implementation of sedekah bumi occurs annually through three main activities: cleaning the streets and rivers, a cultural parade followed by a communal meal, and a shadow puppet (wayang kulit) performance. This study aims to explore how sedekah bumi serves as a medium for social interaction among religious communities in Kalimangli Subvillage, Karang Tengah Village, Tuntang District. The research adopts a qualitative descriptive research method, employing social interaction theory and social action as analytical tools. The findings reveal that sedekah bumi acts as a medium for social interaction among people of different religions. It is evident that all residents of Kalimangli Subvillage, regardless of their religious background, come together to collectively clean the streets and rivers, prepare offerings, create ceremonial structures, and participate in a cultural parade. They wear traditional attire and celebrate the occasion with a wayang kulit performance that emphasizes universal values and human virtues rather than focusing on a particular religious narrative.